Ribosome-associated pentatricopeptide repeat proteins function as translational activators in mitochondria of trypanosomes - Aphasizheva, Inna (Mol Microbiol, 2016)
Mitochondrial ribosomes of Trypanosoma brucei are composed of 9S and 12S rRNAs, eubacterial-type ribosomal proteins, polypeptides lacking discernible motifs and approximately 20 pentatricopeptide repeat (PPR) RNA binding proteins. Several PPRs also populate the polyadenylation complex; among these, KPAF1 and KPAF2 function as general mRNA 3′ adenylation/uridylation factors. The A/U-tail enables mRNA binding to the small ribosomal subunit and is essential for translation. The presence of A/U-tail also correlates with requirement for translation of certain mRNAs in mammalian and insect parasite stages. Here, we inquired whether additional PPRs activate translation of individual mRNAs. Proteomic analysis identified KRIPP1 and KRIPP8 as components of the small ribosomal subunit in mammalian and insect forms, but also revealed their association with the polyadenylation complex in the latter. RNAi knockdowns demonstrated essential functions of KRIPP1 and KRIPP8 in the actively respiring insect stage, but not in the mammalian stage. In the KRIPP1 knockdown, A/U-tailed mRNA encoding cytochrome c oxidase subunit 1 declined concomitantly with the de novo synthesis of this subunit whereas polyadenylation and translation of cyb mRNA were unaffected. In contrast, the KRIPP8 knockdown inhibited A/U-tailing and translation of both CO1 and cyb mRNAs. Our findings indicate that ribosome-associated PPRs may selectively activate mRNAs for translation.